Improving physicians' performance with a stroke CDSS: A cognitive fit design approach. (January 2016) - Chang, Te-Min; Kao, Hao-Yun; Wu, Jen-Her; Su, Yu-Feng
Abstract: A large body of evidence over many years suggests that clinical decision support systems (CDSSs) can be helpful in improving both clinical outcomes and adherence to evidence-based guidelines. CDSSs have however failed to show their effectiveness due to poor ease of use and integration within clinical workflows. This research therefore emphasizes a cognitive fit design approach to developing an effective CDSS to solve those issues. According to the cognitive fit theory CDSS should align with the problem and task representation in order to match the physician's mental model to reduce cognitive effort. Several guidelines based on the cognitive fit design are proposed. A stroke CDSS prototype following the design guidelines is developed to demonstrate its feasibility. The system usability test results showed that the developed stroke CDSS was acceptably accurate, able to lessen the cognitive effort as desired, and preferable for use due to the significant reduction in cognitive load. The developed artifact has shown the potential to benefit physicians. Finally, implications and conclusions are discussed. Highlights: CDSS design guidelines are developed based on cognitive fit theory, SOAP, and CPGs. The guidelines fit physicians' mental models in the problem-solving process. CDSS designed with the guidelines improves physicians' assessment performance. CDSS designed with the guidelines reduces cognitive effort and load. The design guidelines are useful in helping practitioners develop effective CDSSs.